Natural Regeneration in Strychnos nux-vomica L. A Commercially Important Non-Timber Forest Product of Tropical Dry Deciduous Forest - Mohanty, A.; Behera, M. C.; Mohanty, T. L. (Indian Forester, 2020)
Forest is a very complex and dynamic ecosystem and stability of species mainly governed by regeneration success in community. A study was conducted in Chandaka-Damapara wild life sanctuary, Odisha to evaluate the status of natural regeneration of Strychnos nux-vomica in and around canopy of mother tree. A total 16 plots of 1 Ã— 1 m size was laid out per tree at fourdistances (1, 4, 7 and 10 m distances from the trees) in four directions (east, west, south and north) for thirty trees spreading over six sites (Andharua, Sundarpur, Daspur, Kochilaberena, Deras and Ambakhali). Observations on new recruits, un-established seedlings (< 2.0m height) and established regeneration (>2.0m height) were taken in predetermined quadrats and compared for canopy diameter and PAR (Photosynthetically active radiation). Mean number ofregenerates per m2 per tree was recorded 7.56. Maximum number ofrecruits was observed at 7.0 m distance from mother tree receiving PAR 872.40 Î¼molm-2S-2. Survivability of new recruits at the end of growing season was poor within canopy spread area of mother tree. Only 0.50 established regenerates per m2 per tree were observed.